2019
DOI: 10.3389/fimmu.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Screen Identifies Factors Involved in S. aureus-Induced Human Neutrophil Cell Death and Pathogenesis

Abstract: Staphylococcus aureus is a commensal organism in approximately 30% of the human population and colonization is a significant risk factor for invasive infection. As a result of this, there is a great need to better understand how S. aureus overcomes human immunity. Neutrophils are essential during the innate immune response to S. aureus, yet this microorganism uses multiple evasion strategies to avoid killing by these immune cells, perhaps the most catastrophic of which is the rapid induction of neutrophil cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Interestingly, lukGH is upregulated in human blood and the promoter is preferentially activated following exposure to PMNs ( 58 , 59 ). Moreover, a genome-wide screen identified LukGH as a prominent effector of PMN lysis caused by USA300 ( 26 ). DuMont et al identified CD11b as the cell surface receptor for LukAB (also known as LukGH) and showed that cytolysis of host cells by this leukocidin occurs through binding of CD11b on the cell surface ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lukGH is upregulated in human blood and the promoter is preferentially activated following exposure to PMNs ( 58 , 59 ). Moreover, a genome-wide screen identified LukGH as a prominent effector of PMN lysis caused by USA300 ( 26 ). DuMont et al identified CD11b as the cell surface receptor for LukAB (also known as LukGH) and showed that cytolysis of host cells by this leukocidin occurs through binding of CD11b on the cell surface ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…This annotated array of ~2000 mutants of all non-essential genes in the S. aureus JE2 background is a rich resource to investigate staphylococcal physiology. In its 96-well format, the library has been the basis for several phenotypic screens exploring the effects of individual mutations on various aspects of staphylococcal biology, including, but not limited to, S. aureus pathogenesis [12,13], adaptation to and survival of the host environment and corresponding stresses [14,15], and bacterial ability to withstand antimicrobials [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…NADPH oxidase and myeloperoxidase rapidly generate superoxide and HOCl which have strong antimicrobial properties (7,8). Despite these antimicrobial strategies, neutrophils fail to eliminate internalised S. aureus completely (9)(10)(11). Visualising dynamic host-pathogen interactions on a individual subcellular level, as opposed to in fixed samples and on a cell population level, allows us to better understand how S. aureus circumvents the neutrophil response and ultimately reveal pathways to therapeutically target to promote immunity during S. aureus infections.…”
Section: Introductionmentioning
confidence: 99%